ASSESSMENT OF BACTERIAL LOAD OF SOME SELECTED EATING TABLES OF UDUSOK MINI MART - BELLO, A.Y; JUMARE, F.I.; HUSSEIN, R.A.; HARUNA, Z.A.; SANUSI, A.; NAFI’U, A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Bacteria can be found in every nook and cranny of our environment thus, food and its premises are potential mediums causing harm to public health. Bacterial load on eating tables of Usmanu Danfodiyo University Mini market was evaluated. About 13 Samples (single table per shop) were collected from the mini-mart. The moistened sterile swab stick (two per table) was swabbed on each eating table, placed in a 5ml peptone water-containing test tube, shaken, labeled, and transported to the laboratory. Eating shop-table varies by a given capital letter per line and a number per shop. Nutrients agar and standard plate counts was employed. The mean heterotrophic bacteria counts HBC ranged from 2.35×103 to 1.55×105, 2.6×105 to 3.35×106, 4.65×104 to 3.25×106, 2.65×104 to 3.65×106, 3.35×103 to 4.9×105 Cfu/table size for A, B, C, D and E eating-shop line respectively. Best observed colonies were re-cultured, purified and obtain pure isolates. Following the conventional procedure; cultural, morphological, microscopic and biochemical characteristics, the isolates were identified as Listeria spp, Pseudomonas spp, Enterobacter spp, Klebsiella spp, Staphylococcus spp, Serratia spp, E. coli, Corynebacterium spp, Acinetobacter spp, Shigella spp, Helicobacter spp, Campylobacter spp and Citrobacter spp. The bacteria occurrences in the study include Pseudomonas spp, Enterobacter spp, and Citrobacter spp 11.76% each, Listeria spp and Staphylococcus spp had 17.64% each while E. coli 29.41% had greater occurrences. It was clear that Udusok mini-mart eating tables sanitary practices need to be improved for public health concerned.